Human and Islamic Education: Analysis of Tarbawi's Interpretation of Human Nature in QS. Al-'Alaq/ 96: 1-5 - Rahardja, Muhammad Nurfaizi Arya; Amrullah, Alfian; Yamin, Sabanul; Sudi, Ahmad; Cucu Surahman (Geneologi PAI: Jurnal Pendidikan Agama Islam, 2024)
This study focuses on the concept of humanity in Islamic education, particularly through a tarbawi interpretation analysis of QS. Al-‘Alaq/96:1-5. The background of the research is based on the view that humans are unique beings with intellectual and spiritual potential, with an innate tendency to learn and depend on Allah SWT. The purpose of this study is to examine the essence of humans as learning beings who rely on God. This research uses a qualitative method with a descriptive-analytical approach, involving an in-depth interpretation of QS. Al-‘Alaq/96:1-5 through literature review. The research steps include theme determination, relevant verse selection, analysis of classical and contemporary interpretations, and presentation of findings descriptively. The main findings reveal two key aspects of human nature: as beings who constantly learn and as beings who are perpetually dependent on Allah SWT. These aspects underscore the importance of a continuous learning process in Islam, grounded in the values of monotheism, where knowledge serves as a means to draw closer to God.